MODEL KEPEMIMPINAN PENDIDIKAN DIREKTIF DAN INTRUKSIONAL - Didit Kurniadi; Euis Fidyana; Fuad Abdul Baqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify concepts of educational leadership with a focus on directive and instructional leadership models. Through a literature review, the study examines the essence and characteristics of both leadership models. A deep understanding of directive and instructional leadership is expected to make a positive contribution to the development of leadership practices in the field of education. The research method employed in this study is a literature review involving the analysis of recent and relevant literature on educational leadership, particularly in the context of directive and instructional leadership models. The results of the analysis are integrated to form a comprehensive understanding of the key aspects of both leadership models. The findings of this study indicate that directive leadership is a form of leadership that provides followers with clear expectations, schedules the tasks to be carried out, and offers specific guidance on how to complete those tasks. Meanwhile, instructional leadership focuses on students’ learning processes and outcomes through the professional empowerment of teachers. Keywords: educational leadership, directive leadership, instructional leadership, literature review.